Safety and efficacy of ixekizumab in patients with PsA and previous inadequate response to TNF inhibitors: week 52 results from SPIRIT-P2. (24th July 2018) - Genovese, Mark C; Combe, Benard; Kremer, Joel M; Tsai, Tsen-Fang; Behrens, Frank; Adams, David H; Lee, Chin; Kerr, Lisa; Nash, Peter
Abstract: Objectives: To assess the long-term safety and efficacy of ixekizumab, an IL-17A antagonist, in patients with active PsA. Methods: In SPIRIT-P2 (NCT02349295), patients ( n = 363) with previous inadequate response to TNF inhibitors entered the double-blind period (weeks 0–24) and received placebo or ixekizumab 80 mg every 4 weeks (IXEQ4W) or every 2 weeks (IXEQ2W) following a 160-mg starting dose at week 0. During the extension period (weeks 24–156), patients maintained their original ixekizumab dose, and placebo patients received IXEQ4W or IXEQ2W (1:1). We present the accumulated safety findings (week 24 up to 156) at the time of this analysis for patients who entered the extension period ( n = 310). Exposure-adjusted incidence rates (IRs) per 100 patient years are presented. ACR responses are presented on an intent-to-treat basis using non-responder imputation up to week 52. Results: From week 24 up to 156 (with 228 patient years of ixekizumab exposure), 140 [61.3 IR] and 15 (6.6 IR) patients reported infections and serious adverse events, respectively. Serious adverse events included one death and four serious infections. In all patients initially treated with IXEQ4W and IXEQ2W at week 0 (non-responder imputation), ACR20 (61 and 51%), ACR50 (42 and 33%) and ACR70 (26 and 18%) responses persisted out to week 52. Placebo patients re-randomized to ixekizumab demonstrated efficacy as measured by ACR responses at week 52. Conclusion: During the extension period, the overall safety profile of ixekizumab remained consistent with that observed with the double-blind period, and clinical improvements persisted up to 1 year.